2017
DOI: 10.3748/wjg.v23.i19.3449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heme oxygenase-1-modified bone marrow mesenchymal stem cells on microcirculation and energy metabolism following liver transplantation

Abstract: AIMTo investigate the effects of heme oxygenase-1 (HO-1)-modified bone marrow mesenchymal stem cells (BMMSCs) on the microcirculation and energy metabolism of hepatic sinusoids following reduced-size liver transplantation (RLT) in a rat model.METHODSBMMSCs were isolated and cultured in vitro using an adherent method, and then transduced with HO-1-bearing recombinant adenovirus to construct HO-1/BMMSCs. A rat acute rejection model following 50% RLT was established using a two-cuff technique. Recipients were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 68 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…Isolation, culture, and characterization of BMMSCs were performed according to previously described methods [24,27]. Briefly, BMMSCs were isolated from the femur and tibia of male SD rats and cultured in a cell culture incubator.…”
Section: Preparation and Identification Of Ho-1/bmmscsmentioning
confidence: 99%
“…Isolation, culture, and characterization of BMMSCs were performed according to previously described methods [24,27]. Briefly, BMMSCs were isolated from the femur and tibia of male SD rats and cultured in a cell culture incubator.…”
Section: Preparation and Identification Of Ho-1/bmmscsmentioning
confidence: 99%
“…TGF-beta accelerates the formation of fibrous wraps and separates inflamed tissue from normal tissue, to reduce the formation of inflammatory granulation tissue, 70 while the increase of HO-1 can effectively inhibit the excessive action of osteoclasts. [71][72][73] Macrophages of the M1 and M2 phenotypes are indispensable in osteogenesis. Therefore, some scholars suggested that the key factor in determining macrophage-induced osteogenic or osteoclastic effects is the macrophage switch pattern rather than the specific macrophage phenotype.…”
Section: Pro-inflammatory and Pro-regenerative Gene Expression And Elmentioning
confidence: 99%
“…Similarly, an in vitro study by Park and coworkers also revealed that a conditioned medium (CM) derived from fPMSCs could effectively reduce the expression of muscle atrophy-related proteins in myocytes, inhibit the production of ROS, and increase the expression of antioxidant enzymes. Mechanistically, recently studies have demonstrated that the nuclear factor erythroid-derived 2-like 2- (Nrf2-) Kelch-like ECH-associated protein 1- (keap1-) antioxidant response element (ARE) signaling pathway is one of the most important cellular defense mechanisms against oxidative stress [15, 16]. In this respect, MSCs modified with heme oxygenase-1 (HO-1) could enhance paracrine production of hepatocyte growth factor (HGF), interleukin- (IL-) 10, and the activity of Nrf2 to attenuate lipopolysaccharide- (LPS-) induced oxidative damage in pulmonary microvascular endothelial cells (PVECs) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, recently studies have demonstrated that the nuclear factor erythroid-derived 2-like 2- (Nrf2-) Kelch-like ECH-associated protein 1- (keap1-) antioxidant response element (ARE) signaling pathway is one of the most important cellular defense mechanisms against oxidative stress [15, 16]. In this respect, MSCs modified with heme oxygenase-1 (HO-1) could enhance paracrine production of hepatocyte growth factor (HGF), interleukin- (IL-) 10, and the activity of Nrf2 to attenuate lipopolysaccharide- (LPS-) induced oxidative damage in pulmonary microvascular endothelial cells (PVECs) [16]. In addition, the marrow mesenchymal stem cell- (BMSC-) mediated alleviation of bleomycin-induced pulmonary fibrosis was found through a mechanism by activating the HO-1 expression and the Nrf2 pathway [15].…”
Section: Introductionmentioning
confidence: 99%